(untitled) (Fiep Bulletin - online, 2011)
Bone is a multifunctional tissue that answers to a variety of stimuli, such as biological, biochemical and biomechanical ones. Physical activities, mainly those which offers mechanical impacts are considered as initiator of the cycle of bone remodelling. Ooforectomyzed female rats have been used as animal model to osteoporosis studies. Physical activity is considered important for the prevention and treatment of osteoporosis and there are no doubts about the advantages of the exercise to health, at a general view, there are no evidences that exercise on itself could remove the negative effects of the hypoestrogenism. The purpose of this study was to evaluate the effects of high intensity physical training on the bone mass of ooforectomyzed animals Wistar female rats aged approximately 50 days were randomly assigned into four groups of 8-10 animals, according ooforectomy and physical training: sedentary control (C), trained control (TC), sedentary ooforectomyzed (O) and trained ooforectomyzed (TO). During twelve weeks the animals of TC and TO groups followed a high intensity physical training protocol. The training started 40 days after the ooforectomy, and it consisted of four sets of 10 jumps/day in a swimming pool, with the water level corresponding to 150% of the body length and overload equivalent to 50% of the body’s weight. Sedentary ooforectomyzed female rats presented higher weight gain from those of sedentary control group. There was significant decreasing of bone mass in the group of trained ooforectomyzed females. The levels of serum and urinary calcium didn’t present differences in relation to sedentary control group, while the serum phosphorus was smaller in sedentary ooforectomyzed group and trained ooforectomyzed in relation to sedentary control group. Physical training with the load, intensity and duration used here didn’t provide protection to loss of osseous mass in bone mass of female rats with hypoestrogenism.